TRADITION OF THE KARO ETHNICITY IN PERBARAKAN VILLAGE, PAGAR MERBAU DISTRICT - pangesti, giva nisa (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
This study about “ Manuk Sangkep ” in the village firefighting, sub-district Merbau fence, Deli Serdang district, Manuk Sangkep this is a typical Karo dish in the form of chicken cooked with typical Karo spices is served and eaten as a form of appreciation and prayer for someone. Describe values traditional